In Vitro Digestibility and Rumen Fermentation Parameters of Feeds as Affected by Supplementary Amla Powder and Fenugreek Seeds - Kumar, Dinesh; Singh, Putan; Chaturvedi, V. B.; Verma, A. K. (Indian Journal of Animal Nutrition, 2018)
The present study was designed to ascertain the effect of amla(Phyllanthus emblica L.) fruit powder (AFP) and fenugreek (Trigonella foenum-graecum L.) seeds (FS) supplementation on ruminal feed degradability,methane and microbial biomass production (MBP) under in vitro conditions. Concentrate mixture and wheat straw in 60: 40 ratio (on DM basis) was taken as substrate for the experiment. AFP, FS or AFP + FS mixture (1: 1 ratio) was added at 1, 2 and 3% of the substrate, respectively. Digestibility of DM and OM improved (P<0.01) from 57.85±0.62 to 64.42±0.74% and from 65.68±1.24 to 73.90±1.63%, respectively on AFP supplementation. The same trend was also observed for FS and AFP-FS mixture supplementation to the substrate. Total gas (ml/g DM) production after 24 h incubation varied from 118.49±3.00 to 129.14±2.50 (AFP), 113.26±4.87 to 125.86±2.66 (FS) and from 128.05±0.92 to 139.89±2.84 (AFP-FS mixture) in comparison to the control (111.95±1.13). The values of MBP was significantly (P<0.05) higher in AFP and FS supplemented substrates. Therefore, it was concluded that supplementation of AFP, FS and AFP + FS improved DM and OM digestibility microbial biomass production while reducing methane production in vitro.